Two illicit dark web marketplaces taken down. Issue 8 (August 2017) - Unknown
Abstract : Police forces around the world have cooperated on operations that have resulted in the take-down of two major dark web marketplaces and also allowed them to gain control of a number of vendor accounts for a third.